The Effectiveness of Electronic Trials in the Jurisdiction of the District Court Semarapura Class II Based on Supreme Court Regulation Number 7 of 2022 - I Komang Merta Ardiasa; Made Subawa; Zuhro Nurindahwati (Pusat Publikasi Nusantara, 2024)
Electronic trials, also known as e-trials, represent a significant innovation in the judicial process by integrating technology into court proceedings. These trials utilize digital platforms to manage and conduct various aspects of the trial process, including the submission of evidence, witness testimonies, and legal arguments. However, the adoption of electronic trials also presents challenges that must be carefully considered. This study aims to determine the effectiveness of electronic trial in the jurisdiction of the Semarapura District Court Class II based on Perma Number 7 of 2022, and the obstacles experienced in its implementation. The research contributes to a deeper understanding of the challenges that courts may face in adopting such systems, thereby offering critical information that could inform future improvements and policy adjustments.